Work environment of the veterinary surgeons of Thrissur district for extension activities under panchayati raj - Shubhangi Baburao Tajne (Department of Extension, College of Veterinary and Animal Sciences, 2003)
The veterinary surgeons, as part of their roles, performing extension work under Panchayati Raj, were studied to under stand the work environment as well as to explore the relationship between the perception of the work environment and commitment to PRI. A total of 103 veterinary surgeons of the AHD, and working in Thrissur district of Kerala state formed the sample. As tools of the study, questionnaires, interview schedules, and group interviews were used. The results indicated veterinary surgeons' general dissatisfaction with the prevailing work environment to perform extension work. To be specific, except for the dimension interpersonal and client relation, all others were found to be relatively lesser- satisfied ones, the lowest ranked dimension being responsibility and risk taking. Moreover, those fully satisfied in the job were not even one-fifth of the total studied, and those satisfactorily committed to PRI, only a little above one-fifth. The dimensions, communication, services and supplies, peoples' participation and local leadership, work distribution and team work as well as planning and execution of projects were positively and significantly correlated with commitment to PRI. Therefore, these were more important dimensions of work environment from the perspective of commitment to PRI. Evenso, the dimensions services and supplies as well as work distribution and teamwork were much more important, since both contributed positively and significantly to the variability in commitment to PRI. ~ Force field analysis revealed that the only weak driving force to be lack of . enough youth and woman participants in animal husbandry development projects. The most important solution suggested to strengthen this force was implementing more of viable self-employment projects that could attract youth and woman increasingly into the development process. But there were more of strong inhibiting forces namely delayed clearance of projects, delayed funding, delayed beneficiary identification, defective beneficiary identification, lack of proper arrangement for training development staff, panchayat authorities' inability in